Exploitation of heterosis and combining ability in cucumber (Cucumis sativus) for earliness and yield contributing traits - BISHT, YASHPAL SINGH; SINGH, D K; BHATT, RAJENDRA; RAWAT, ANAND SINGH; KUMAR, MUKESH; SINGH, SHASHANK SHEKAR; BISHT, CHARU (The Indian Journal of Agricultural Sciences, 2025)
The present experiment was conducted during the rainy (kharif) seasons 2021 and the summer season of 2022 at Govind Ballabh Pant University of Agriculture and Technology, Pantnagar, Uttarakhnad to investigate the earliness, yield, variation and its effect on cucumber (Cucumis sativus L.). The present study comprised of 30 F1 hybrids, developed by line × tester, crossing 10 lines (gynoecious) i.e. PPCUC-2 and PPCUC-3 (parthenocarpic gynoecious line developed by GBPUA&T, Pantnagar), PPCUC-4, PPCUC-5, PPCUC-6, PPCUC-7, PPCUC-9, PPCUC-10, PPCUC-11 and PPCUC-12 and 3 testers (monoecious) parents viz. PCUC-8, PCUC-28 and PCUC-51. A significant difference for mean sum of square was found in all the horticultural traits under study. PPCUC-2 and PPCUC-9 were superior for earliness and PPCUC-3 was best general combiner for yield, which can be used as a parent in breeding programme for development of genoecious × monoecious hybrids. In the cross combination, PPCUC-2 × PCUC-28 for earliness and PPCUC-7 × PCUC-8 is found best hybrids for yield. PPCUC-3 × PCUC-28 was best specific combiner for fruit number. Information of gene actions obtained from the study indicated the predominance of non-additive gene action which is highly desirable to develop hybrids in cucumber with yield traits. Based on heterosis, PPCUC-2 × PCUC-28 and PPCUC-9 × PCUC-28 were most promising crosses for earliness and yield contributing traits. Based on finding, it is also possible to segregate generations using promising hybrids in order to find pure lines with high yields and superior quality fruit.